What drives companies to do good? A "universal" ordering of corporate social responsibility motivations. (31st August 2021) - Lim, Alwyn; Pope, Shawn
Abstract: The classic question of why companies do corporate social responsibility (CSR) is central to much theoretical, regression‐based, and experimental research. Guiding research into this question is a tripartite schema of normative, instrumental, and political CSR motivations that has become increasingly established in the CSR literature. This paper challenges the schema's status as a typology of equally plausible alternatives through an integration and analysis of a worldwide literature of 120 existing academic surveys on CSR motivation. Rather, the paper reformulates the schema into a surveyed ordering of CSR motivations that might be called "universal" in having remarkable stability across time periods, industries, company sizes, geographic regions, question formats, types of survey respondents, and types of survey producers. The paper challenges the schema also by documenting robust internal heterogeneity that it conceals, particularly where instrumental motivations are concerned, which are among the most and least self‐selected CSR motivations in our results.